Leading Difficult Conversations Series #1: Introduction - Christy Chiarelli (EDIS)
This publication series examines strategies and tactics for leaders to utilize when tasked with having a difficult conversation. Leadership can require leaders to have necessary conversations that are not always easy. Through providing leaders with specific tools to have difficult conversations, this series aims to promote dialogue and equip individuals to be more successful leaders. The series provides information regarding preparing for difficult conversations, creating a safe conversation environment, utilizing conversation tactics, and employing listening skills. This new 2-page publication of the UF/IFAS Department of Agricultural Education and Communication is part 1 of the series. Written by Christy Chiarelli. https://edis.ifas.ufl.edu/wc374